Penerapan Metode Student Centered Learning Tipe Small Group Discussion dalam Pembelajaran Fisika Terapan Taruna Teknika Nautika - Lusiani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Akademi Maritim Nusantara Cilacap, 2021)
This study aims to provide an overview of the application of the student centered learning method type of small group discussion in applied physics learning for nautical engineering cadets. The method in this study is a survey and literature review. The research object was cadets in the engineering and nautical study program of AMN Cilacap. Learning outcomes in the psychomotor domain are obtained through the discussion method. The instrument used is using google classroom media. Based on the appearance of each image, a small group discussion step in the applied physics learning of nautical techniques is described. Steps 1 to 6 are shown in Figures 1 to 17. In the Engineering class, it can be seen in Figures 3, 4, 7, 8, 9, 10. Whereas in the Nautical class, it can be seen in Figures 5, 6, 11, 12, 13, 14, 15, 16, 17. Applied physics learning in the Nautical class is more enthusiastic and active using small group discussions, whereas in the Engineering class it looks standard (in general). After analyzing and discussing it, it was concluded that the student centered learning method of the small group discussion type in applied physics learning by nautical engineering cadets can be applied according to the 6 steps in the small group discussion.